TAKWA DALAM AL-QUR’AN SURAH ALI IMRAN AYAT 102 MENURUT M. QURAISH SHIHAB - Lita , Lita; Hasanah, Syarifah (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2020)
Taqwa is an effort to carry out acts of obedience to Allah because of faith and expecting a reward from Allah because of His commands and prohibitions. The background of this research is to know the meaning of piety according to M. Quraish Shihab and how the method used by M. Qurasih Shihab to interpret it. The purpose of this study is to objectively explain: 1) The meaning of piety according to M. Quraish Shihab Q.S. Ali Imran verse 102, 2) What is the method of interpretation of M. Quraish Shihab on the meaning of piety in Q.S. Ali Imran verse 102. This type of research is library research. This research consists of primary data and secondary data. While the data collection technique in this research is a documentary study, namely collecting notes, books, journals, and written materials both in print and electronically regarding matters related to this research. The results of this study note that the meaning of piety according to M. Quraish Shihab in the Qur'an Surah Ali Imran verse 102, explains the true peak of piety. Through this surah, humans are encouraged to be pious, and are ordered to strive towards the right path, so that they get the grace according to their efforts. Surah Ali Imran is a guide to the right path. The method of interpretation used by M. Quraish Shihab in Tafsir Al-Misbah is the tahlili method. Explaining the meaning of the verses of the Qur'an from various points of view, according to the order of verses and suras in the manuscripts by prioritizing the content of lafazh, interrelation (munasabah) between verses and surahs, asbabun nuzul, related traditions, and opinions of the scholars. previous commentators.